APPLICATION OF MICROPROCESSOR SYSTEMS IN AUTOMOTIVE INDUSTRY - V. G. Mikhailov (Системный анализ и прикладная информатика)
Questions of application of microprocessor systems for their automation are considered an automation condition on existing designs of truck. It is noticed that now the majority of truck exhausted in the CIS are automated only partially. By automation are captured: control, preliminary treatment of a condition of systems and the information on them; control of start, partially control by power-plant work; control of sprinkling fuel; control of power supply; control of brakes, antiblocking systems, airbags; climate control maintenance; illumination.Scopes of microprocessor systems in cars and microcontrollers used for this purpose taking into account that now it is required to expand areas of automation of systems of cars considerably are considered. The analysis of systems and the functions which are subject to automation for truck and special cars is carried, questions of application of microprocessor systems for reception of experimental data on roads (microprofile and longitudinal cross-section) and their use at car modelling, and also maintenance of road safety: distance maintenance between cars, control of blind zones; an exception засыпания the driver during movement, reduction of harmful influence from noise and vibrations.It is offered complexing realised functions and systems of their control. The short description and a substantiation of expediency of application of means of automation on the basis of the cheap microprocessor modules Arduino is given, allowing considerably to reduce quantity of used microcontrollers. Block diagrammes of realisation of problems of traction dynamics in package MatLab/Simulink, transformations and horizonting of truck and special cars by means of MC Arduino are resulted. Recommendations to introduction of systems of automation for truck and special cars are made.